Kuby immunology - Punt, Jenni (W H Freeman, 2019)
The 8th edition of 'Kuby Immunology' presents an up-to-date and comprehensive introduction to the principles and findings of immunology. It contains full-colour illustrations, study questions, study aids and much more.